Outcomes of Operative Treatment for Adult Cervical Deformity: A Prospective Multicenter Assessment With 1-Year Follow-up. Issue 5 (21st December 2017) - Ailon, Tamir; Smith, Justin S; Shaffrey, Christopher I; Kim, Han Jo; Mundis, Gregory; Gupta, Munish; Klineberg, Eric; Schwab, Frank; Lafage, Virginie; Lafage, Renaud; Passias, Peter; Protopsaltis, Themistocles; et al.
Abstract: BACKGROUND: Despite the potential for profound impact of adult cervical deformity (ACD) on function and health-related quality of life (HRQOL), there are few high-quality studies that assess outcomes of surgical treatment for these patients. OBJECTIVE: To determine the impact of surgical treatment for ACD on HRQOL. METHODS: We conducted a prospective cohort study of surgically treated ACD patients eligible for 1-yr follow-up. Baseline deformity characteristics, surgical parameters, and 1-yr HRQOL outcomes were assessed. RESULTS: Of 77 ACD patients, 55 (71%) had 1-yr follow-up (64% women, mean age of 62 yr, mean Charlson Comorbidity Index of 0.6, previous cervical surgery in 47%). Diagnoses included cervical sagittal imbalance (56%), cervical kyphosis (55%), proximal junctional kyphosis (7%) and coronal deformity (9%). Posterior fusion was performed in 85% (mean levels = 10), and anterior fusion was performed in 53% (mean levels = 5). Three-column osteotomy was performed in 24% of patients. One year following surgery, ACD patients had significant improvement in Neck Disability Index (50.5 to 38.0, P < .001), neck pain numeric rating scale score (6.9 to 4.3, P < .001), EuroQol 5 dimension (EQ-5D) index (0.51 to 0.66, P < .001), and EQ-5D subscores: mobility (1.9 to 1.7, P = .019), usual activities (2.2 to 1.9, P = .007), pain/discomfort (2.4 to 2.1, P < .001), anxiety/depression (1.8 to 1.5, P = .014). CONCLUSION: Based on a prospective multicenter series of ACD patients, surgical treatment provided significant improvement in multiple measures of pain and function, including Neck Disability Index, neck pain numeric rating scale score, and EQ-5D. Further follow-up will be necessary to assess the long-term durability of these improved outcomes.